AHP-based geospatial analysis for landslide susceptibility zonation in Wayanad District - Irshad Tharayil; T Harikrishnan; Bose Mahalingam; Kurniati Titi (E3S Web of Conferences)
Landslide susceptibility zonation mapping is a decision-making process that entirely depends upon the land use and land cover changes from one point to another. The accuracy and precision of the study related to the quality of the parameters used to determine the occurrence and intensity of the landslides. This study acquired secondary data from Landsat-8 satellite images and GSI (Geological Survey of India). The landslide conditioning factor was assigned with the help of the semi-quantitative Analytical Hierarchy Process (AHP) Technique. In this current study, 13 parameters were analyzed. Each parameter is responsible for landslides in a low or high influence grade. Each parameter was designed to have a particular weight based on its influence on landslide occurrence. Rainfall is the prime factor for the landslides in the Wayanad district. The final landslide susceptibility zonation map was validated using appropriate mathematical treatment to check their correctness with the help of landslide inventory points.